Investigar el periodismo taurino - Forneas Fernández, María Celia (Estudios sobre el Mensaje Periodístico, 2008)
Investigation is always a difficult task. Investigation of the bullfighting world is something really crazy. The question is that the majority of the inhabitants in the bullfighting planet believe that their truth is the TRUTH. In the beginning, everything is magic and mysterious; later controversies appear and much more having in mind that we fight against two serious problems: journalism and bullfighting world.
Keywords: Investigation; Journalism; Bulls